Bulk and Surface Characterization of Linixcoymn2-X-Yo4+Delta (X, Y=1/ 3 1/4) Synthesized by Sol-Gel and Sol-Gel Ultrasound Assisted Methods - Gautier-Zamora, J; Gautier-Zamora, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D (ELSEVIER SCIENCE BV, 2018)
Oxides LiNixCoyMn2-x-yO4+delta d (x, y = 1/3, 1/4) were synthesized at 800 degrees C by sol-gel (SG) and sol-gelassisted ultrasound (UASG) methods. The Rietveld refinement of the XRD data indicated that all the compounds crystallize in the spinel structure and allowed to propose the corresponding cation distributions. SEM and TEM images showed that the oxides prepared by both methods consist of irregular polyhedra in the submicron size range. The samples prepared by UASG have both higher surface areas and Li+ ion diffusion coefficients than those synthesized by the SG method. XPS studies of these oxides reveal the presence of Ni2+, Ni3+, Co3+, Mn3+ and Mn4+ ions on the surface. (C) 2018 Elsevier B.V. All rights reserved.